Articulation between information systems and quality management systems: literature review - Ferreira, Sílvia G. G. (2012)
Technological advancement has influenced all aspects of daily life. Since the adoption of Information Technology (IT) / Information Systems (IS), that represents the key issue for the success of most organizations, management of the quality of its products, services and business processes with established quality certification under ISO 9000, also represents a critical aspect in organizations. Organizations are forced to use advanced technologies and become more efficient in internal organization in order to be more competitive and closer to their customers and partners. In the face of increasingly demanding markets, interventions for organizational improvement through the adoption of quality management are becoming very common. The organizations are concerned with the development and implementation of information systems tailored to their specific needs, rather than buying in the market software applications. By the other hand, organizations acquire software certificates on the market to meet some specific requirements of the Quality Management Systems (QMS), such as auditing and document management. Synergies between the IS and QMS according to ISO 9001 standard, allows the association between these two systems, so that the IS can support and influence the processes related to the QMS, not only limited to the collection and documentation management. The joint development of these systems allows organizations to use only a methodology and a team intervention. The potential benefits of active participation of the organizational processes associated with the IS / QMS raises the need to develop a method that articulate/integrate interventions for improvement motivated by IT / IS with the improvement interventions motivated by the QMS.